Bank Specific Determinants of Bank Profitability in Indonesia for The Period 2008-2019 - Muhammad Luthfi Utomo; Achmad Herlanto Anggono (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2020)
Banks have an important role in the economy and are the significant driver of economic growth for its financing to many industries in the economy. Thus, banks need to be maintained profitable to keep operating and avoid the major impact of bank failure. This study attempts to know the relationship between bank-specific variables of Liquid Assets to Total Assets (LATA), Non-performing Loans to Total Loans (NPLTL), Operating Cost to Operating Income (OCOI), Third-party funds to Total Assets (TPFTA), and Core Capital Tier 1 to Total Assets (TIER1TA) toward bank profitability by using Return on Assets (ROA) and Return on Equity (ROE) as the measure. The data used are 7 banks of BUKU 4 category for the period 2008-2019 in quarterly frequency. The research uses panel data regression of the fixed-effects model. The findings show that LATA is significant negative to ROA and ROE, NPLTL is significant positive to ROA and ROE, OCOI is significant negative to ROA and ROE, TPFTA is significant positive to ROA and ROE, and TIER1TA is significant negative toward ROA and ROE. Banks should maintain their operating expense low, increase their interest income, and getting a source of funds with low cost to get more profit.